108k views
5 votes
5(3x2 + ?x - 2) = 15x2 - 20x - 10

User Jamal Aziz
by
5.3k points

1 Answer

2 votes

Let's start:


5(3x^2+?x-2)=15x^2-20x-10

To find the coefficient missing here, you simply have to use ''multiply and divide property of equality'' and ''add and subtract property of equality'':


\begin{gathered} 15x^2+5?x-10=15x^2-20x-10 \\ \text{the same terms on the both sides, so you can eliminate them , then:} \\ 5\text{?x}=-20x \\ ?=(-20x)/(5x) \\ ?=-4 \end{gathered}

User Jwize
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.